Effects of Electrode Materials on Power Generation of Microbial Fuel Cell - E., Baranitharan; Khan, Maksudur R.; D. M. R., Prasad; Jailani, Salihon (2013)
Energy shortage and environmental pollution mainly caused the global energy crisis which led to serious impact on human survival and development. Microbial fuel cells (MFCs) exactly meet the requirements to alleviate the global energy crisis because it has the ability to treat the wastewater and produce electricity concurrently. MFCs are considered as one of the promising technology in the wastewater treatment technology. The power output depends on various factors such as substrate degradation, electrode material, rate of electron transfer from bacteria to the anode, circuit resistance, proton mass transfer in the liquid, external operating conditions and so on. Electrode material is one of the key factors which affect the performance of MFC. Therefore, it is of great significance to select and develop suitable electrode materials to optimize and promote the performance of MFCs. Each electrode material has its own physical and chemical properties such as surface area, electric conductivity and chemical stability. In this research, we have tested two different electrode materials such as; polyacrlyonitrile carbon felt (PACF) and single forward carbon cloth (SFCC) to study the effects of different electrode materials on MFC performance. The results showed that MFC with SFCC using raw POME showed high power density (102.5mW/m2) compared to PACF (45mW/m2). But COD removal efficiency with raw POME of SFCC (43%) and PACF (45%) were not shown much difference. The coulombic efficiency of 1:50 diluted POME reached upto 26% for SFCC whereas for PACF 24% was achieved. SFCC achieved the highest coulombic efficiency and power output than PACF, indicating SFCC facilitate the biofilm formation and improve power generation.